8. Phytochemical Screening and Antibacterial Activity, Antilarvacides and Toxicity Test of Acetone Extract Pulutan Leave (Urena lobata) - Siska Juita Gea; Tita Juwitaningsih; Ida Dumariris; Murniaty Simorangkir; Destria Roza (Jurnal Medika Veterinaria, 2021)
This study aims to determine the content of secondary metabolites, antibacterial activity, antilarvicides, and pulutan leaf acetone extract toxicity test. Photochemical tests were carried out using several suitable reagents. Bacterial activity test using disc diffusion and microdilution methods against Salmonella typhi and Streptococcus mutans bacteria, then toxicity test using the BSLT method. Larvicide test by observing the mortality of Aedes aegypti larvae for 24 hours. Based on the phytochemical tests, pulutan leaves contain flavonoids, alkaloids, steroids, saponins, and tannins. The results of the antibacterial activity test showed activity against S. typhi and S. mutans with inhibition zone diameters of 7.05 mm and 8.25 mm, respectively. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values against S. typhi and S. mutans were 5000 g/mL and 5000 g/mL, respectively. The toxicity test results of pulutan leaf acetone extract had an LC50 value of 37.20 ppm, while the results of the larvicidal activity test had an LC50 value of 1971.19 ppm. The toxicity test results showed that the acetone extract of pulutan leaves was toxic and not anti-larvicidal to A. aegypti larvae. The bioactivity ability of pulutan leaf acetone extract is influenced by the content of flavonoids, alkaloids, steroids, saponins, and tannins. It can be concluded that the pulutan leaf extract in the Nias area has the potential as a source of antibacterial compounds